The Dogs of War - Forsyth, Frederick (Random House Group, 1974)
An astonishing discovery is made in the remote African republic of Zangaro, one which could change the course of a nation's history forever. But such a discovery cannot be kept secret for long and Sir James Manson will stop at nothing to protect this find. A ruthless and bloody-minded tycoon, Manson immediately hires an army of mercenaries and with this deadly crew behind him he sets out to topple the government and replace its dictator with a puppet president. But news of the discovery has reached Russia - and suddenly Manson finds he no longer makes the rules in this power game. A game in which win or lose means life or death.
Keywords: Fiction